Strategi Pemberdayaan Sentra Usaha Kecil dan Menengah Budidaya Ikan Lele Menggunakan Matriks Internal-Eksternal, Analisis SWOT, dan Matriks Perancangan Strategi Kuantitatif - Hendang Setyo Rukmi; Irfan Khairullah; Ratna Puspitaningsih (President University, 2016)
The village of Karanganyar, at the regency of Indramayu, is the largest centre for walking catfish aquaculture industry in West Java. However, during 2015-2016, the growth of the catfish aquaculture has not been satisfactory, mostly due to several obstacles that reduces the production rate by 25%. Therefore it is necessary to map out an empowerment strategy for the aquaculture industry of catfish in the village of Karanganyar. The process of designing the strategy uses Internal-External Matrix (IE), analysis on Strength, Weakness, Opportunities and Threats (SWOT), and Quantitative Strategic Planning Matrix (QSPM). Early step involves gathering internal (strength and weakness) and external factors (opportunities and threats) for the aquaculture industry of catfish. These factors points to the factor that affects the development of the industry. Second step involves determining the empowerment strategy for the aquaculture industry of catfish in accordance to internal and external conditions using IE Matrix and SWOT analysis. Third step requires establishing a scale of priority for the prioritised strategy, which includes 1) forming a union of catfish farmer, 2) consolidate and reinforce partnership with institutions of higher education, supporting organisations, and other supporting institutions, and 3) developing capabilities of processing catfishes to satisfy demands from local and international markets. First strategy is expected to overcome the dependency on third parties for fishmeal, markets, and capitals, along with the difficulties for accessing financial institutions. Second strategy is expected to help with the development of the product, the improvement on the standardisation of aquaculture and post-harvesting activities of catfishes, and the step-up on levels of independency for farmers in terms of capital and funding. Third strategy is expected to grab the market niche and opportunity for catfish-based products in national and international scale by exploiting the ease of access to the market, the availability of training and supporting program for catfish aquaculture industries, and good ratings from customers in regard to the quality of catfishes produced by the industry.